The Center for Surgical Health: A Compassion-Driven Urban Surgical Mission. (November 2021) - Scire, Emily; Morales, Carrie Z.; Herbst, Alan; Goldshore, Matthew; Morris, Jon B.
We are the Center for Surgical Health (CSH), an academic community partnership that supports, educates, and advocates for vulnerable Philadelphians with surgical diseases, founded in 2016 by Dr. Jon B. Morris, a leader in surgical education and a general surgeon at the University of Pennsylvania, and Dr. Alan Herbst, a current third-year Penn general surgery resident. At the time, Dr. Morris, raised in a Reform Jewish household, had been participating in an RCIA Program to convert to Catholicism. The mission of providing surgery to uninsured patients, primarily undocumented individuals, by helping them obtain insurance and see Penn providers was seen by Dr. Morris as a form of Catholic charity, which he has continued to remain dedicated to as his faith in Jesus Christ has deepened. Dr. Herbst, now Associate Director of Clinics for the CSH, recalls working with Dr. Morris as a sub-intern during his conversion, beginning with passion and a neon poster board inviting people to "See the Surgeon." Since that time, the CSH has grown from an organization with 10 volunteers, called "personal patient navigators, " who provide insurance support and advocacy at every step of the perioperative continuum, to one with over 50, who have now seen 156 patients and assisted in providing 49 needed procedures. Much of this growth has been brought about through the dedication and vision of Dr. Matthew Goldshore, the Deputy Director of the CSH and a fifth-year Penn general surgery resident, as well as Dr. Carrie Z. Morales, Associate Deputy Director of the CSH and a recent Perelman School of Medicine graduate. Through their leadership, and the talent and commitment of other members of the CSH board, overseen by Director Dr. Morris, the CSH now has policy and research divisions, a surgical equity curriculum, and continues to develop new ways of providing better care.